Walking the talk? Teachers' and early years' practitioners' perceptions and confidence in delivering the UK Physical Activity Guidelines within the curriculum for young children. Issue 1 (2nd January 2019) - Howells, Kristy; Meehan, Catherine
ABSTRACT: This study explored early years' practitioners' and teachers' attitudes and confidence in delivering the UK Physical Activity guidelines [National Health Service (NHS). (2013). Physical activity guidelines for children and young people . Retrieved July 15, 2015, fromwww.nhs.uk/Livewell/fitness/Pages/physical-activity-guidelines-for-young-peopole.aspx ] within the curriculum for young children [Department for Education (DfE). (2013). The national curriculum in England. Key stages 1 and 2 framework document . London: Department for Education, Crown; Department for Education (DfE). (2014). Statutory framework for the early years' foundation stage. Setting the standards for learning, development and care for children from birth to five . London: Department for Education, Crown]. Using an online questionnaire, data were analysed using thematic framework and statistically. Fifty-nine respondents came from early years' settings, including nurseries, pre-schools and primary schools. The findings suggest that there is a lack of confidence in knowing what to do to support and sustain physical activity. Further research is needed to identify if this is a national trend; this is the next steps of our research, as is the development of resources to help support confidence and the delivery of physical activity for young children.